Catalytic liquid marbles : Ag nanowire-based miniature reactors for highly efficient degradation of methylene blue - Miao, Yue-E (2014)
Ag nanowire-based catalytic liquid marbles are fabricated as miniature reactors, which demonstrate highly efficient, support-free and rate-controllable heterogeneous degradation of methylene blue, with catalytic efficiency close to 100%. Our miniature catalytic liquid marbles are essential for reactions involving highly toxic/hazardous or costly reactants, where small volume preliminary reactions are preferred.